Active versus passive distraction for reducing procedural pain and anxiety in children: a meta-analysis and systematic review - Ting Shen; Xixi Wang; Qiaoyun Xue; Dan Chen (BMC, 2023)
Abstract Background Procedural pain is very important in clinical children care. We aimed to evaluate the effects of active versus passive distraction for reducing procedural pain and anxiety in children. Methods Two researchers searched the Web of Science, PubMed, EMBASE, Cochrane, SinoMed, Wanfang, China National Knowledge Infrastructure, Weipu databases for the randomized controlled trials(RCTs) on the active versus passive distraction affecting procedural pain and anxiety in children until May 18, 2023. The literature screening and data extraction were carried out by two researchers independently. Review Manager 5.3 software was used for data analysis. Results 13 RCTs were finally included. 553 children received active distraction intervention and 551 children received passive distraction intervention. There were no significant differences in the children self-reported procedural pain betweent active and passive distraction. The parent-reported procedural pain, medical staff-reported procedural pain, children-reported procedural anxiety, parent-reported procedural anxiety, medical staff-reported procedural anxiety in the active distraction were significant less than that of active distraction. Egger regression analysis showed that there was no publication bias in the results. Conclusions Existing evidence suggests that active distraction may be more effective in reducing operational pain and anxiety in children than passive distraction. More studies on the effects of active distraction versus passive distraction in children with larger sample size are needed in the future.